EXISTENTIALIST FEMINISM IN LAUREN SCHMIDT HISSRICH’S THE WITCHER (2019) - Panji Kusumondanu (LITERA KULTURA : Journal of Literary and Cultural Studies, 2021)
The purpose of this study is to examine the gender discrimination in Lauren Schmidt Hissrich’s The Witcher (2019). It explains what gender discrimination suffered by the female main character, Yennefer, and what actions did she take to rise from gender discrimination in film. Gender discrimination toward women is still happening in our society, and people still not being aware of this women's oppression issue. Yennefer is suffering gender discrimination toward women in the movie. Because of her gender, Yennefer has only seen her based on her appearance. When she doesn’t meet people’s standards of beauty, she was seen as a creature with no value. This study is a feminist analysis that applies Simone de Beauvoir’s (2010) existentialist feminism theory as well as Timothy Heiderich’s (2012) and Warren Buckland’s (2015) cinematographic language. The findings show that Yennefer is suffering from gender discrimination toward women. She is mistreated because of her appearance. When Yennefer realize that she can rise from the gender discrimination she suffered, she decided to take her chance and freed herself from her condition.